Roald Amundsen and his Ambiguous Relationship to Science: A Look at Outcomes of his Six Expeditions - Elzinga, Aant (Journal of Northern Studies, 2012)
Roald Amundsen’s active life as an explorer coincided with a period of important changes in the earth sciences. The purpose of the present paper is to situate some of his endeavours in relation to those trends. On the one hand there was a continuation of empirical traditions in field sciences driven by the same inductivist approach that motivated the First International Polar Year 1882–1883. On the other hand there were major advances in instrumentation, plus a strong professionalization of research. The latter involved new mathematical methods used by hypothesis-minded geophysicists who probed the dynamics of physical processes. In this context Amundsen was what Fridtjof Nansen called a “scientific explorer.” The paper traces some of the tensions engendered in this role midway between two scientific trends while at the same time the explorer’s public image followed the tradition of popular geography steeped in nationalism and prestige that drove the steeplechase of being first to set one’s foot on and attach names to hitherto undiscovered places. It is shown how several of Amundsen’s expeditions resonated strongly with contemporary trends and interests in scientific societies, especially in Norway. At the same time he was pulled between loyalty to Fridtjof Nansen and science and an unending quest for recognition and media visibility as a dashing explorer. Since much has been written about Amundsen’s sportive and adventurous side, not least in connection with the dramatic race to the South Pole, the focus in the present paper is chiefly on his relationship to science, an aspect often glossed over. First Amundsen’s position as a reflective practitioner is characterized and highlighted. Secondly, the Norwegian and international scientific contexts of his expeditions are sketched, and, third, an assessment is made of the scientific outcomes of the projects he initiated and their uneven reception over time in a number of disciplines, since he left it to others to translate data into science while he himself restlessly moved on to the next challenge. It is found that although never a scientist himself, Amundsen’s initiatives generated considerable amounts of empirical data that was of value once it was reduced, analysed and interpreted by professional scientists. Perhaps even more importantly, his expeditions or projects helped further the scientific careers of a number of brilliantly resourceful persons.